CERITA RAKYAT DARI BALI: BEBERAPA KEJANGGALAN LINGUISTIS - I Dewa Putu Wijana (Humaniora, 2004)
This paper aims to show the role of linguistic competence in the Indonesian folk tale writing activities, especially the writer for whom Balinese is not his or her native language. Some linguistic mistakes found in the story book entitled "Cerita Rakyat dari Bali" indicate that the linguistic competence is as important as the cultural knowledge has to be owned by every writer. The linguistic clumsiness will certainly disturb the smoothness of the story telling and the nature of the folk tales.